Determinants of Elderly Health Service Utilization in Mangunrejo Village, Wonorejo Health Center Working Area Ngadiluwih District, Kediri Regency - Ismiaty, Emy; Puspitasari, Yenny; Nurwijayanti, Nurwijayanti (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT National data in 2016, the utilization of elderly posyandu was only 5.39% with an increase of 13.23% in 2017. The proportion of elderly people served in East Java Province fluctuated, in 2016 it was 62, in 2017 it decreased by 49 and increased again in 2018 by 75%. Meanwhile, data on elderly health services at Wonorejo health centers in 2022 amounted to 63.4%. This data shows the lack of utilization of posyandu services for the elderly. The aim of this research is to analyze the determinants of utilization of posyandu services for the elderly in Mangunrejo Village, Wonorejo Health Center Working Area, Ngadiluwih District, Kediri Regency. This type of research is Observational Analytical. This study used a cross-sectional design. Respondents were taken using purposive sampling technique. Population of all elderly people in Mangunrejo Village, Wonorejo Health Center Working Area, Ngadiluwih District, Kediri Regency. The sample size was 253 people. Independent variables are service quality, attitudes and cadre roles. The dependent variable is the use of posyandu services for the elderly. Statistical tests use Logistic Regression.service quality was in the good category, namely 158 people (62.5%). the attitude of respondents in the negative category was 137 people (54.2%). the role of cadres in the good category is 140 people (55.3%). The utilization of elderly posyandu services is in the good category, namely 156 people (61.7%), the influence of service quality on the utilization of elderly posyandu services with a significance value of 0.003 <0.05. the influence of attitudes on the use of posyandu services for the elderly with a significance value of 0.001 < 0.05, the influence of the role of cadres on the use of posyandu services for the elderly with a significance value of 0.023 < 0.05. there is an influence of service quality, attitudes and roles of cadres on the utilization of posyandu services for the elderly in Mangunrejo Village, Wonorejo Health Center Working Area, Ngadiluwih District, Kediri Regency. Keywords:Service Quality, Attitude, Role of Cadres, Elderly Posyandu